Inovasi Strategi Elaborasi Mindfullnes untuk Meningkatkan Efektivitas Layanan BK dengan Deep Learning pada MGBK SMK Kabupaten Tegal - Yunita Dwi Setyoningsih; Argo Widiharto; Farikha Wahyu Lestari; Ismah Ismah (Pelita: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of digital technology in the 21st century has had a significant impact on education, including the emergence of moral degradation, increasing individualism, and instant-living tendencies among students. These conditions contribute to academic pressure and psychosocial problems, requiring more comprehensive guidance and counseling services. The implementation of deep learning within the Merdeka Curriculum serves as a strategic approach to strengthening students’ character and resilience; however, its application remains limited because many counseling teachers have not yet fully developed adequate emotional regulation and social awareness skills. The integration of elaborative mindfulness strategies into deep-learning–based counseling services offers a promising solution by emphasizing non-judgmental awareness, enabling counselors to be fully present, empathetic, and able to create a conducive counseling atmosphere. This community engagement program aims to enhance the understanding and skills of counseling teachers in integrating both approaches. A total of 71 counseling teachers participated in the program. The method used was Participatory Action Research (PAR) conducted over two weeks, consisting of five stages: (1) Diagnosing, identifying key partner issues such as difficulties in analyzing the needs of Generation Z and Alpha students and the lack of understanding of deep learning; (2) Action Planning, designing interventions through seminars, lectures, demonstrations, and online mentoring; (3) Action Taking, conducting training sessions with expert speakers; (4) Evaluating, assessing the impact of the interventions through open-ended questionnaires; and (5) Specifying Learning, documenting insights gained from both the successes and challenges of the implementation process. The results show an increase in teachers’ understanding from a score of 22.02 to 27.65. These findings highlight that strengthening the competencies of counseling teachers through contextual and collaborative approaches effectively supports the integration of deep learning and mindfulness in guidance and counseling services.